Hotspots in hydrogen research and developments: Current status, pathways, challenges, and vision to 2050 - Driss Belkhiri; Mohamed Ajaamoum; Fatima Outferdine; Abdellah El idrissi; Elmahfoud Boulaoutaq (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The climate crisis and global warming have created an urgent need for the scalable adoption of affordable and clean energy sources to achieve net-zero carbon emissions by 2050. Decarbonization of global industries is critical to achieving the targets of the Paris Agreement and the United Nations Sustainable Development Goals (especially Goals 7 and 13). Green hydrogen is becoming a key solution in the transition to renewable energy and the decarbonization with low-carbon energy options. This review presents an overview of the status and trends of hydrogen production, storage, transportation, and application, as well as key research areas with a forward-looking perspective to 2050. It explores the key challenges, such as limited infrastructure, high production costs, and heavy energy demands. The study also identifies the drivers and barriers influencing hydrogen adoption across utility-scale electricity generation, heating, and niche markets. Key actions of governments in these pillar areas are necessary to accelerate hydrogen deployment through strategic investments and a policy framework to reduce technological costs and drive innovation. Transformative innovation in power generation, transportation, industrial processes, and infrastructure will be essential to achieving deep decarbonization. In addition, progress in digitalization, automation, data-driven decision-making, recycling incentives, and circular economies are essential to a social transformation and a global transition toward sustainability. Emerging hydrogen markets are also playing an increasingly dominant role in economic and human development, particularly in low- and middle-income countries, as the world works to transition to the use of renewable hydrogen.